The Legality of Lontong Kupang Culinary Tourism Typical of Sidoarjo Regency Against the Improvement of the Community's Economy Based on Islamic Law - Bawa Mulyono Hadi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
This qualitative research aims to elucidate the legal aspects and economic impact of Kupang rice cake culinary tourism on community income within the Sidoarjo Regency area, as viewed through the lens of Islamic law. Data were collected from Kupang rice cake entrepreneurs using direct observation, interviews, and documentation. Data analysis involved techniques of data reduction, presentation, and verification. The study reveals significant findings: firstly, Kupang rice cake culinary tourism profoundly influences the income of the local community; secondly, the presence of Kupang Lontong culinary tourism directly contributes to the local economy by generating employment opportunities for the surrounding population. This economic role creates job opportunities for both skilled staff and laborers, thus benefiting the community; thirdly, from the perspective of Islamic law, the existence of Kupang rice cake culinary tourism aligns with the provisions of halal nafsihi (permissible for self) and halal ghoirihi (permissible for others). Culinary tourism falls under the category of mutual assistance, fostering opportunities for shared work and business, and can be regarded as a recommended (sunnah) practice. This study provides insights into the positive economic and legal dimensions of Kupang rice cake culinary tourism, contributing to the understanding of the compatibility of such ventures with Islamic legal principles and their potential to enhance community welfaret